Prevalence and Regional Differences in Migrated Hips in Danish Children with Cerebral Palsy from 2008 to 2021-A Comparison of Ambulant vs. Non-Ambulant Children - Muhammed Bakhtiyar; Afrim Iljazi; Michael Mørk Petersen; Anders Odgaard; Christian Wong (MDPI AG, 2024)
Purpose: This study aims to assess the incidence of hip displacement and dislocation (denominated as hip migration) among ambulant and non-ambulant Danish children with cerebral palsy (CP) by estimating their cumulative incidence of migrated hips. A secondary objective is to compare the prevalence across different Danish regions. Methods: Data were obtained from the Danish Cerebral Palsy Follow-Up Program (CPOP) from the years 2008 to 2021. This population-based cohort study included 1388 children with CP (58% male; 42% female) as subjects; aged 0-15 years; with an average age of 5.4 years at their last follow-up. The children were categorized according to their Gross Motor Function Classification System (GMFCS) level into ambulators (GMFCS I-III) and non-ambulators (GMFCS IV-V). The Kaplan-Meier estimator was employed to calculate the cumulative incidence of migrated hips from birth until the date of their last radiographic follow-up. Differences between ambulatory and non-ambulatory children and regional differences were assessed with the Log-rank test. Results: Median radiological follow-up for ambulators was 51 months and 94 months for non-ambulators. The cumulative incidence of hip dislocation was 0.3% (95% CI: 0-0.8%) and 22.0% (95% CI: 9.2-34.8%) for ambulators and non-ambulators, respectively (p < 0.0001), whereas the incidence of hip displacement was 21.1% (95% CI: 16.3-25.9%) and 76.7% (95% CI: 68.6-84.7%) for ambulators and non-ambulators, respectively (p < 0.0001). There were no significant regional differences in the incidence of hip dislocation among ambulators, but there were significant differences for non-ambulators. Moreover, significant regional differences were detected in hip displacement for both ambulators and non-ambulators. Conclusions: The prevalence of hip migration in Danish children with CP is significantly higher among non-ambulators, who are at an increased risk of hip migration compared to their ambulant counterparts. However, the low frequency of radiographic follow-up for ambulators might cause the incidence of hip migration to be underestimated. This study highlights the necessity of continued targeted surveillance and interventions in Danish non-ambulators.